The Influence of Market Attractiveness and Unique Capability on Collaboration Strategy and Business Performance: A Study at Digital Creative Industry in Java - Lizardo, Jimmy; Colline, Fredella (Journal The Winners, 2023)
The creative industry has been a fundamental part of the digital economy, but its profitability remained low, at less than 25% per year. Therefore, the research aimed to ascertain the impact of market attractiveness and unique capabilities on the collaboration strategy, along with their implications for the business performance of Java’s digital creative sector. The population was digital creative industry players in Java Island which focused on the Games, Education, Digital Music, Animation, Software, and Social Media sectors (GEMASS). The sample taken was 50 respondents from the total population as many as 106 legalized digital creative industry players who had been established for more than 3 years. Data were processed using Partial Least Square (PLS-SEM). The findings show that both market attractiveness and unique capability positively and significantly influence collaboration. Market attractiveness has no effect on business performance but has an indirect effect through collaboration strategy. Unique capability positively and significantly affect business performance both directly and indirectly through collaboration strategy. Collaboration strategy positively and significantly affect performance, which is greater than the direct effect of unique capability. Digital creative industry in Java Island are suggested to prioritize the implementation of collaboration strategy that is built with unique capability and consider the market attractiveness.